Pengembangan Media Pembelajaran Interaktif Berbasis Video (Powtoon) pada Pelajaran Teknik Dasar Administrasi Perkantoran Kelas X OTKP di Smk Tunas Pembangunan - Rahayu Sulistio Putri; Henry Eryanto; Roni Faslah (Jurnal Syntax Admiration, 2024)
This research aims to develop video-based interactive learning media (Powtoon) for the subject of Basic Engineering of Office Administration in class X OTKP SMK Tunas Pempembangunan and evaluate its feasibility. This research uses the type of R&D (Research and Development) research. The Research and Development method is useful in producing a video-based interactive learning media product and the use of R&D research will test the feasibility of the product made. Results: Developing Powtoon's interactive video-based learning media using research and development (R&D) methods, also known as Research and Development. ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. This research only came to development because of a very limited time. The results of the eligibility of media experts were 73% with the category of "Feasible", while the results of the feasibility of material experts were 96% with the category of "Very Feasible" which was carried out at SMK Tunas Pempembangunan .